Framing of Maternal and Child Healthcare Issues in Nigerian Newspapers - Adeniran, Raheemat (2020)
The mass media are important for wide dis-semination of health information. The frame of reference adopted in the reportage of health issues tends to influence people’s perception towards health related issues. Studies examin-ing framing of health issues have found the me-dia wanting in their reportage of health. This study extends the frontier of framing analysis of health coverage in the media by examin-ing framing of maternal and child healthcare (MCH) issues in Nigerian newspapers. Using the content analyses method, two categories of frames - public health frame, and coping versus alarm message frame - were examined in the study. Four national newspapers were purposively sampled over a 12-month period resulting in the analysis of 1,235 MCH-relat-ed editorial items. The study found minimal adoption of public health frame with only 12% adoption rate, and dominant adoption of cop-ing frame over alarm frame with rare combi-nation of both. The findings reflect the impli-cation of greater reliance on official sources for health stories in the media, resulting in lack of context in reported stories to aid proper un-derstanding of issues. The study calls for better framing of health related issues in the media to generate appropriate attention to possibly drive development in the health sector.